Decorating vertically aligned MoS2 nanoflakes with silver nanoparticles for inducing a bifunctional electrocatalyst towards oxygen evolution and oxygen reduction reaction. (March 2021) - Solomon, Getachew; Kohan, Mojtaba Gilzad; Vagin, Mikhail; Rigoni, Federica; Mazzaro, Raffaello; Natile, Marta Maria; You, Shujie; Morandi, Vittorio; Concina, Isabella; Vomiero, Alberto
Abstract: Catalysts capable of improving the performance of oxygen evolution reaction (OER) and oxygen reduction reactions (ORR) are essential for the advancement of renewable energy technologies. Herein, Ag-decorated vertically aligned MoS2 nanoflakes are developed via magnetron co-sputtering and investigated as electrocatalyst towards OER and ORR. Due to the presence of silver, the catalyst shows more than 1.5 times an increase in the roughness-normalized rate of OER, featuring a very low Tafel slope (58.6 mv dec −1 ), thus suggesting that the catalyst surface favors the thermodynamics of hydroxyl radical (OH) adsorption with the deprotonation steps being the rate-determining steps. The improved performance is attributed to the strong interactions between OOH intermediates and the Ag surface which reduces the activation energy. Rotating ring disk electrode (RRDE) analysis shows that the net disk currents on the Ag-MoS2 sample are two times higher at 0.65 V compared to MoS2, demonstrating the co-catalysis effect of silver doping. Based on the rate constant values, Ag-MoS2 proceeds through a mixed 4 electron and a 2 + 2 serial route reduction mechanism, in which the ionized hydrogen peroxide is formed as a mobile intermediate. The presence of silver decreases the electron transfer number and increases the peroxide yield due to the interplay of a 2 + 2 electron reduction pathway. A 2.5–6 times faster conversion rate of peroxide to OH - observed due to the presence of silver, indicating its effective cocatalyst nature. This strategy can help in designing a highly active bifunctional catalyst that has great potential as a viable alternative to precious-metal-based catalysts. Graphical Abstract: ga1 Highlights: Surfaces modification of MoS2 nanoflakes with Ag nanoparticles generates higher oxidation states. A 2.5–6 times faster conversion rate of the peroxide to OH - is observed, due to the presence of silver. Silver is an effective cocatalyst, which speeds up the reduction of the intermediate peroxide much faster than bare MoS2 . In situ, RRDE measurement revealed the ORR on Ag-MoS2 mainly proceeds via a 2 + 2 serial route. Ag multifunctional catalytic properties allow MoS2 to induce bifunctional properties for both OER and ORR.